Description of the spontaneous repair of the internal rectus abdominis muscle sheath and peritoneum in dogs. surgical implications - Doriman Geme, Saul; Dorfman, Denny; cardozo, José; Rivas, Lorena; Mora La cruz, Eduardo (Revista Científica de la Facultad de Ciencias Veterinarias, 1970)
Thirty female dogs underwent abdominal surgery, which consisted of a lateral and transverse incision below the umbilical scar in order to ascertain the healing of the peritoneum and internal rectus abdominis muscle sheath by secondary intention based on the premise that healing of peritoneal defects depends on the proliferation of the underlying connective cells, whereas aponeurosis heals by ingrowth of cells from the cut edges. The wound was closed by suturing the external aponeurosis of the rectus abdominis muscle and the skin. The animals were sacrificed at days 1,3,8 and 90 days after surgery. The scar tissue was studied microscopically. Wound healing was complete at 90 days because two different mechanisms of repair contribute to a common healing process. The absence of wound dehiscense and incisional hernia in the animals allows to conclude that in the closure of the abdominal wall, the peritoneum and the internal rectus abdominis muscle sheath have little relevance in the healing process and the subsequent strength of the laparotomy scar.